2018
DOI: 10.1111/gcb.14513
|View full text |Cite
|
Sign up to set email alerts
|

Climate change does not affect the seafood quality of a commonly targeted fish

Abstract: Climate change can affect marine and estuarine fish via alterations to their distributions, abundances, sizes, physiology and ecological interactions, threatening the provision of ecosystem goods and services. While we have an emerging understanding of such ecological impacts to fish, we know little about the potential influence of climate change on the provision of nutritional seafood to sustain human populations. In particular, the quantity, quality and/or taste of seafood may be altered by future environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…Therefore, oceanographic habitat suitability predictions for kingfish would be of high value to fishers who aim to target the highest quality fish possible for the purpose of consumption, and who are willing to modify their behaviour to achieve this goal. Comparisons between phase angle measurements used to assess fish condition herein and various metrics for quantifying seafood quality (Coleman et al, ) could be undertaken to determine whether the range of variation in phase angle measurements corresponds to meaningful changes in kingfish seafood quality. This is a necessary step before links are drawn between oceanographic habitat suitability and the spatial distribution of kingfish seafood quality off eastern Australia and subsequent implications (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, oceanographic habitat suitability predictions for kingfish would be of high value to fishers who aim to target the highest quality fish possible for the purpose of consumption, and who are willing to modify their behaviour to achieve this goal. Comparisons between phase angle measurements used to assess fish condition herein and various metrics for quantifying seafood quality (Coleman et al, ) could be undertaken to determine whether the range of variation in phase angle measurements corresponds to meaningful changes in kingfish seafood quality. This is a necessary step before links are drawn between oceanographic habitat suitability and the spatial distribution of kingfish seafood quality off eastern Australia and subsequent implications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that relationships between seafood quality and environmental habitat suitability would be found for coastal‐pelagic species that associate with dynamic oceanographic features, such as kingfish, than for estuarine species that have evolved broad physiological tolerances to environmental conditions. For example, Coleman et al () found that the seafood quality of a common sparid, yellowfin bream ( Acanthopagrus australis ), was not affected by experimental treatments simulating future climate change scenarios. Coleman et al () attributed the lack of physiological responses in this species to its evolution in estuarine habitats that are characterized by high abiotic variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, relatively few studies have examined the effect of environmental variation on commercially harvested fish condition. For example, the majority of studies investigating linkages between ocean temperatures or acidification and body condition, particularly metrics of nutritional quality, have focused on coastal invertebrates (Anacleto et al., 2014; Champion, Broadhurst, et al., 2020; Tate et al., 2017; Valles‐Regino et al., 2015) with only one study of a commercial fish species published to date (Coleman et al., 2019). Environmental conditions can also affect the organoleptic properties of fish tissues, such as taste, appearance, texture and odour (Watson et al., 1988).…”
Section: Introductionmentioning
confidence: 99%